Industrial Structure and the Comparative Behavior of International Stock Market Indices. - Roll, Richard (Journal of Finance, 1992)
Stock Price Indices are compared across countries in an attempt to explain why they exhibit such disparate behavior. Three separate explanatory influences are empirically documented. First, part of the behavior can be attributed to a technical aspect of index construction; some indices are more diversified than others. Second, each country's industrial structure plays a major role in explaining stock price behavior. Third, for the majority of countries, a portion of national equity index behavior can be ascribed to exchange rate behavior. Exchange rates explain a significant portion of common currency denominated.national index returns, although the amount explained by exchange rates is less than the amount explained by industrial structure for most countries.